Fiscal Taylor rules in the postwar United States - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2009)
Recent research and events have brought fiscal policy back into the spotlight. Fiscal Taylor rules and error correction models have represented two different ways of quantifying the feedbacks from fiscal and economic conditions to fiscal policy decisions. This paper synthesizes these two ideas, estimating a fiscal Taylor rule as a special case of an error correction model. Using quarterly postwar U.S. data, estimates of a fiscal Taylor rule find that the government sector has sought to stabilize its debt through adjustments to purchases and taxes, in that order, with very little stabilization coming through adjustments to transfer payments. Since 1981, the debt-stabilization motive has almost vanished, while the cyclical behavior of fiscal variables has not changed. This provides indirect evidence that fiscal policy may have become "non-Ricardian" in the US during recent decades.
Keywords: E62; E63; H62; H63; 330; Taxation; government spending; transfer payments; fiscal policy; deficits; fiscal Taylor Rule; Finanzpolitik; Taylor-Regel; Haushaltsdefizit; Haushaltskonsolidierung; Sozialtransfer; USA